Samples of Torah Texts in Hadiths and Athar from the Books of the Pure Prophetic Sunnah - Collection and Study – - Salem Khazal Hamad; Ahmed Mudher Abbas (Islamic Sciences Journal, 2025)
There are many texts in the books of the pure Sunnah that have transmitted to us a number of texts from the Torah, also known as the Old Testament. These texts are diverse, including those on belief, predictions of the unseen, legal rulings, morals and etiquette, and descriptions of the Prophet (peace and blessings be upon him) These texts include those traced back to the Prophet (peace and blessings be upon him), those attributed to the Companions, and those transmitted by the Successors from what they read or were transmitted to them from the texts contained in the Torah. These texts include those narrated by Bukhari and Muslim, those narrated by the compilers of the Sunnah, those narrated in Musnads or dictionaries, and those narrated by the compilers of the Hadith collections. These texts have been compiled from the collections of the Sunnah, and those accepted and rejected have been clarified, along with an explanation of the strange terms, the subtleties of their chains of transmission, and the benefits derived from them